2019
DOI: 10.1002/ldr.3419
|View full text |Cite
|
Sign up to set email alerts
|

Varied response of underground and aboveground plant matter: functional diversity of three different vegetational types after translocation to reclaimed postindustrial land

Abstract: The indicators of functional diversity are increasingly used to assess the conservation effectiveness of the most valuable habitats. However, little is known about the response of functional traits, their diversity, and divergence in plant communities after translocation. To assess how functional diversity changes on dry heath, meadow, and fen after translocation of entire turfs of vegetation from an airport area to the Botanical Garden in Radzionków, we used leaf–height–seed (LHS) traits (specific leaf area, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Consistent with most previous studies that reported similar patterns at the top 0 − 10 cm of the soil layer, our results suggest that hydrological regimes can potentially modulate and constrain plant growth, community structure, and stability of alpine meadow ecosystems (Heisler-White et al, 2008;An et al, 2019;Ren et al, 2023), as soil moisture is critical for resprouting and growth of belowground bud banks of all bud types. Additionally, total C, plant diversity, and soil moisture significantly correlated with bud banks, indicating that vegetation and soil physicochemical attributes play crucial roles in ecological succession and productivity output of meadow ecosystems (Hong et al, 2012;Xie et al, 2018;S ́wierszcz et al, 2019;Plue et al, 2021).…”
Section: Land Use Change Alters the Relative Contributions Of Vegetat...mentioning
confidence: 99%
“…Consistent with most previous studies that reported similar patterns at the top 0 − 10 cm of the soil layer, our results suggest that hydrological regimes can potentially modulate and constrain plant growth, community structure, and stability of alpine meadow ecosystems (Heisler-White et al, 2008;An et al, 2019;Ren et al, 2023), as soil moisture is critical for resprouting and growth of belowground bud banks of all bud types. Additionally, total C, plant diversity, and soil moisture significantly correlated with bud banks, indicating that vegetation and soil physicochemical attributes play crucial roles in ecological succession and productivity output of meadow ecosystems (Hong et al, 2012;Xie et al, 2018;S ́wierszcz et al, 2019;Plue et al, 2021).…”
Section: Land Use Change Alters the Relative Contributions Of Vegetat...mentioning
confidence: 99%